2017
DOI: 10.1002/jsfa.8542
|View full text |Cite
|
Sign up to set email alerts
|

Kernel oil content and oil composition in walnut (Juglans regia L.) accessions from north‐eastern Italy

Abstract: The wide variation in fatty acid content and composition allows superior accessions to be selected for diffusion among growers. A suitable strategy would be to make a selection against PUFA content rather than just for high oleic acid. In addition, the selected high oleic accessions, before being utilized per se or as donor parents in breeding programs, have to demonstrate they are not adversely affected by the environment. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
56
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 66 publications
(62 citation statements)
references
References 29 publications
5
56
1
Order By: Relevance
“…The oleic acid content of the eastern area (average value: 15.82%) was lower than the southwestern area and the northwestern area (average value: 19.56% and 19.98%, respectively). Poggetti et al () found that the oleic acid content and the daily temperature had a significant linear relationship and positive correlation. The average air temperature of the eastern area was lower than others, which exhibited the same tendency.…”
Section: Resultsmentioning
confidence: 97%
“…The oleic acid content of the eastern area (average value: 15.82%) was lower than the southwestern area and the northwestern area (average value: 19.56% and 19.98%, respectively). Poggetti et al () found that the oleic acid content and the daily temperature had a significant linear relationship and positive correlation. The average air temperature of the eastern area was lower than others, which exhibited the same tendency.…”
Section: Resultsmentioning
confidence: 97%
“…Moreover, Juglans oil also affects endocrine factors associated with artherosclerosis or chronic inflammation . The beneficial health effects of Juglans oil have been mainly attributed to its high ω‐3 and ω‐6 fatty acids content that are essential for the human diet . It contains more than 70% of polyunsaturated fatty acids (PUFA) and other minor components such as L‐arginine.…”
Section: Introductionmentioning
confidence: 99%
“…The trees were not from commercial varieties. The same trees have been previously characterized by molecular methods (Vischi et al, ) while their fruits have already been analysed by morphological and carpological methods as well as for oil content and composition (Poggetti et al, ). The trees are grouped into five geographically and climatic homogeneous areas: (a) the western Alpine highlands (“Carnic Alps”), (b) the eastern Alpine highlands (“Julian Alps”), (c) the eastern hilly and low mountain area (“Torre and Natisone valleys”), (d) the broad central and southern plains area (“Friuli plains”) and (e) the south‐eastern carbonate plateau (“Trieste Karst”).…”
Section: Methodsmentioning
confidence: 99%
“…The trees were not from commercial varieties. The same trees have been previously characterized by molecular methods (Vischi et al, 2017) while their fruits have already been analysed by morphological and carpological methods as well as for oil content and composition (Poggetti et al, , 2018. The trees are grouped into five geographically and climatic homogeneous areas: (a) the western Alpine highlands Table S1).…”
Section: Studied Walnut Treesmentioning
confidence: 99%
See 1 more Smart Citation